Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/698_2012_161
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in European Cities and Associated Health Impacts

Abstract: Atmospheric nanoparticles are a pollutant currently unregulated through ambient air quality standards. The aim of this chapter is to assess the environmental and health impacts of atmospheric nanoparticles in European environments. This chapter begins with the conventional information on the origin of atmospheric nanoparticles, followed by their physical and chemical characteristics. A brief overview of recently published review articles on this topic is then presented to guide those readers interested in expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…The authors observed the occurrence of new particle formation as a result of the photochemical process ( Figure 6). The high number of particles in the atmosphere over the MASP is related to vehicular emissions, as has been reported for other cities around the world (Kumar et al, 2010;Kumar et al, 2011aKumar et al, , 2013aKumar et al, , 2014, and the amount of black carbon in the lower stages of a cascade impactor has an impact on climate and adverse health effects.…”
Section: Ultra Fine Particles (Ufp)mentioning
confidence: 53%
“…The authors observed the occurrence of new particle formation as a result of the photochemical process ( Figure 6). The high number of particles in the atmosphere over the MASP is related to vehicular emissions, as has been reported for other cities around the world (Kumar et al, 2010;Kumar et al, 2011aKumar et al, , 2013aKumar et al, , 2014, and the amount of black carbon in the lower stages of a cascade impactor has an impact on climate and adverse health effects.…”
Section: Ultra Fine Particles (Ufp)mentioning
confidence: 53%
“…A recent laboratory investigation found total PNCs about ~2.3, 5.2, 20.4, 25.1 (×10 4 ) cm -3 which were ~2, 3, 14 and 17 times over the background during cube crushing, 'wet' recycling, slab demolition and 'dry' recycling, respectively (Kumar et al, 2012c). Our recent study reviewed a total of about 45 sampling locations in 30 different cities within 15 European countries for quantifying levels of roadside PNCs (Kumar et al, 2012a). Average PNCs at the reviewed roadside were found to be 3.8±3.2 ×10 4 cm -3 .…”
Section: Construction and Demolitionmentioning
confidence: 97%
“…A total of 11 major NES are comprehensively evaluated. It should be noted that the road vehicles are intentionally left out of the scope of this article since a number of well documented review articles covering their origin, characterisation, measurement methods, instrumentation, dispersion modelling and their impacts on health, visibility impairment and climate change already exist; see summary of these articles in Kumar et al (2012a) and references therein.…”
Section: Scope Aims and Article Outlinementioning
confidence: 99%
“…Two important species are generally missing so far in the Ei3 database [50] and are also missing in our updated inventory, namely PN (particle number) and BC (black carbon), although emission data are available (e.g., [84]). PN and BC inhalation poses a considerable health risk to humans (e.g., reference [85]). In conclusion, even with our updated real-world-oriented emission profile it is not possible to fully account for all adverse health impacts of diesel car emissions by LCA.…”
Section: Emission Profiles Developmentmentioning
confidence: 99%